Retrotransposon R1Bm endonuclease cleaves the target sequence - Feng, Qinghua (The National Academy of Sciences, 1998)
The R1Bm element, found in the silkworm Bombyx mori, is a member of a group of widely distributed retrotransposons that lack long terminal repeats. Some of these elements are highly sequence-specific and others, like the human L1 sequence, are less so. The majority of R1Bm elements are associated with ribosomal DNA (rDNA). R1Bm inserts into 28S rDNA at a specific sequence; after insertion it is flanked by a specific 14-bp target site duplication of the 28S rDNA. The basis for this sequence specificity is unknown. We show that R1Bm encodes an enzyme related to the endonuclease found in the human L1 retrotransposon and also to the apurinic/apyrimidinic endonucleases. We expressed and purified the enzyme from bacteria and showed that it cleaves in vitro precisely at the positions in rDNA corresponding to the boundaries of the 14-bp target site duplication. We conclude that the function of the retrotransposon endonucleases is to define and cleave target site DNA.